Transnational gentrification and the housing market during pandemic times, Lisbon style - Mendes, Luís (2022)
In the decade between 2009 and 2019, the city of Lisbon was undeniably riding the crest of a wave of international projection as a tourist destination. Simultaneously, its housing market was acquiring financial asset formats and attracting globalized dynamics of demand and foreign investment to bring about transnational gentrification. This process was leveraged by government programs and the neoliberal turn in urban politics, which both fostered the attraction of a transnational elite and favored the financialization of real estate, and thereby aggravating trends in eviction and residential segregation. The breakup of the community and its network of primary neighborhoods, as well as other socio-territorial inequalities brought about by evictions and an overheated rental market, became especially clear due to the Covid19 pandemic. The lack of mutual support networks, formerly provided by the community, has hindered resilience to coronavirus and the city’s capacity for recovery while also exposing the contradictions of an urban growth model for economic recovery that in recent years has centered on overtourism and the financialization of real estate. This paper is structured into two main sections. The first addresses a very brief theoretical framework on transnational gentrification and how touristification became a relevant urban and economic strategy and a consequence of the 2008–2009 capitalist crisis and its aftermath of austerity. This explains the lines of socio-territorial inequality exposed during, and reproduced by, the pandemic crisis. Furthermore, the second section attempts to describe in greater detail the consequences of this overheated housing and rental market that, somewhat incredibly, has still not cooled despite the pandemic crisis, worsening the lack of access to housing and the corresponding rise in homeless people, urban poverty and alongside all the difficulties in servicing the mortgages and rents demanded by this market. This is all further aggravated by setbacks to labor rights due to the pandemic driven economic crisis. The state of emergency that was enacted with mandatory social isolation and lockdown as well as limitations on freedom of movement, resistance and economic activities, relaunched discussions around the right to housing in Portugal. These discussions carry over from the pre-covid context with grassroots movements and local initiatives. This demonstrated how poor access to the right to housing, in the midst of a pandemic crisis, not only turns out to be a condition for worsening the pre-covid socio-territorial inequalities and residential segregation but also an obstacle to full compliance with sanitary standards.